Anti-neutrophlic cytoplasmic antibody Elastase, Lactoferrin, Cathapsin G,and Lysozyme in a sample of Iraqi patients with Rheumatoid Arthritis - Al-Rubaye, Mahmood R. (Journal of the Faculty of Medicine Baghdad, 2015)
mucosal secretions as well as in secondary granules of polymorphonuclear leukocytes. Anti-Elastase antibodies, anti-Lactoferrin antibodies,anti-Cathapsin G antibodies and anti-Lysozyme antibodies, which belong to Perinuclear Anti-Neutrophil Cytoplasmic Antibodies(pANCA) have been described in several immunomediated diseases, including Rheumatoid Arthritis . Objectives: Investigate the prevalence of anti-Elastase antibodies, anti-Lactoferrin antibodies,anti-Cathapsin G antibodies , anti- Lysozyme antibodies and rheumatoid factor in patients with rheumatoid arthritis in comparison to healthy control. Patients &Methods: The study involved 40 Rheumatoid Arthritis patients who were referred to Immunological Department in Teaching laboratory Medical City during period of (1st of January – 31st of June) 2011 and 25 apparently healthy individual used as a control group were investeged to rheumatic factor IgG, IgM ,IgA isotypes and Elastase antibodies, Lactoferrin antibodies, Cathapsin G antibodies , and lysozyme antibodies were measured by using enzyme immunoassay technique. Results : Anti- Elastase, Abs anti-Cathapsin G Abs ,and anti-lysozyme Abs showed significant correlation with RF screen, and the mean concentration for these antibodies in rheumatoid arthritis patients with significant difference if compare it with the healthy control group. While anti-Lactoferrin Abs showed no significant correlation with RF screen. This study showed a association between the positive results of anti- Cathapsin G Abs with RF IgG and RF IgM only .Anti- Elastase Abs, Anti-Lactoferrin Abs and Antilysozyme Abs showed neither a significant correlation with RF IgG, RF IgM nor with RF IgA. Conclusion:A significant correlation was found between Elastase antibodies, Cathapsin G antibodies , lysozyme antibodies and patients with rheumatiod arthritis Cathapsin G antibodies has a significant association with RF IgG and RF IgM